2002
DOI: 10.1074/jbc.m112063200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tumor Necrosis Factor-α-induced Nuclear Translocation and Activation of NF-κB by Dehydroxymethylepoxyquinomicin

Abstract: We previously designed and synthesized an NF-B inhibitor, dehydroxymethylepoxyquinomicin (DHMEQ), that showed anti-inflammatory activity in vivo. In the present study we looked into its mechanism of inhibi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
148
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 204 publications
(164 citation statements)
references
References 44 publications
13
148
2
1
Order By: Relevance
“…We have shown that DHMEQ inhibits NF-kB at the level of nuclear translocation. 15 In the present study, we demonstrate that topoisomerase inhibitors induce NF-kB in not only H-RS cell lines with wild-type IkBa but also in H-RS cell lines lacking wild-type IkBa by activating IKK and constitutive as well as inducible NF-kB are the molecular target of HL treatment by DHMEQ.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…We have shown that DHMEQ inhibits NF-kB at the level of nuclear translocation. 15 In the present study, we demonstrate that topoisomerase inhibitors induce NF-kB in not only H-RS cell lines with wild-type IkBa but also in H-RS cell lines lacking wild-type IkBa by activating IKK and constitutive as well as inducible NF-kB are the molecular target of HL treatment by DHMEQ.…”
supporting
confidence: 57%
“…15 Panepoxydone had been found to inhibit TNF-a-induced activation of NF-kB. We have shown that DHMEQ inhibits NF-kB at the level of nuclear translocation.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…As far as we know, SMMC 7721-CM contains a number of angiogenic factors and cytokines (12), and NF-nB can be activated by many stimuli, including IL-1h (22) and TNF-a (23,24). To identify which factor in SMMC 7721-CM is a major contributor in activating NF-nB through the CD146-induced signal pathway, we tested the effects of IL-1h and TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicated DHMEQ specifically inhibited the NF-κB activating pathway. (18) DHMEQ also inhibited TPA-induced NF-κB activation in Jurkat cells. TPA is considered to activate IKK through the activation of protein kinase C. Therefore, it was suggested that DHMEQ inhibits the NF-κB activation at a level that is downstream of IKK.…”
Section: Naturally Occurring Nf-κ κ κ κB Inhibitors and Discovery Of mentioning
confidence: 83%